Use of Social Media as a Learning Media in 21st Century Learning - Hidir, Ahmad; Malik, Rahman; Bekata, Halena Muna; Waruwu, Yaredi; Syarofa, Najwa (Al-Hijr: Journal of Adulearn World, 2023)
Today's rapidly growing use of social media has both positive and negative impacts on people's social lives. Moreover, based on UNESCO data, Indonesian people are very active in using social media. This research aims to The use of social media as a learning medium aims to increase students' interest in learning, improve students' ability to use technology and increase students' awareness in using social media in the context of education. The method used in this research is a quantitative method using a survey model and in-depth interviews with one teacher and students. The results of this study show that social media can be used for learning tools or media. However, in reality, currently there is no maximum use of social networking media. The results of researchers' observations by looking at the growing phenomenon, that the use of social networking media is currently mostly only used by students to be limited to sending messages with friends, playing games (games), and buying goods online. The use of social networking media is currently still not utilized as a learning medium by students. The conclusion of this research is that media in the learning process is an inseparable part of the teaching and learning process in order to achieve an educational goal in general and learning objectives. Strategies to be able to find learning media. The right and appropriate in the learning process can be done by making considerations in the selection of social media. Therefore, the limitation of this study is that researchers only conducted research on the role of the Discovery Learning strategy in Islamic cultural history lessons, researchers hope that future researchers can conduct research on the Discovery Learning strategy by developing this strategy in other subjects.